Historia badań nad zagadnieniem najstarszych zachodnich sanktuariów męczenników. Od kontrreformacyjnej apologetyki po współczesne badania interdyscyplinarne - Stróż, Anna (Vox Patrum, 2013)
In the course of centuries the Early Christian sanctuaries of the martyrs either continued their purpose and remained the sacred destinations or fell into ruin and became forgotten. There was not much interest in the study of them, at least until the XVIth century, the Counter-Reformation period, when the evidence of sources was used as a weapon to defeat the opponents of the cult of the saints. Ipso facto the study has become only a devotional enterprise. Religiously oriented investigations of Early Christian sanctuaries became more scientific later, with the development of the Christian archaeology, as it gradually separated from theological studies. The remains of the monuments finally started to be regarded as a precious heritage, which should be carefully excavated, documented and well preserved. With G.B. de Rossi’s work the interest in the subject of Christian archaeology increased. Initiated by him the huge archaeological campaign spread in the latin West and goes on till present day. The recent research challenge is to make the picture of the earliest sanctuaries more clear by removing the confessional additions and trying to face the sources in broader, interdisciplinary context.